Nutritional, Economic, and Environmental Costs of Milk Waste in a Classroom School Breakfast Program - Blondin, Stacy A. (Am J Public Health, 2017)
Objectives. To measure fluid milk waste in a US School Breakfast in the Classroom Program and estimate its nutritional, economic, and environmental effects. Methods. Fluid milk waste was directly measured on 60 elementary school classroom days in a medium-sized, urban district. The US Department of Agriculture nutrition database, district cost data, and carbon dioxide equivalent (CO(2)e) emissions and water footprint estimates for fluid milk were used to calculate the associated nutritional, economic, and environmental costs. Results. Of the total milk offered to School Breakfast Program participants, 45% was wasted. A considerably smaller portion of served milk was wasted (26%). The amount of milk wasted translated into 27% of vitamin D and 41% of calcium required of School Breakfast Program meals. The economic and environmental costs amounted to an estimated $274 782 (16% of the district’s total annual School Breakfast Program food expenditures), 644 893 kilograms of CO(2)e, and 192 260 155 liters of water over the school year in the district. Conclusions. These substantial effects of milk waste undermine the School Breakfast Program’s capacity to ensure short- and long-term food security and federal food waste reduction targets. Interventions that reduce waste are urgently needed.